2021
DOI: 10.31850/makes.v4i2.817
|View full text |Cite
|
Sign up to set email alerts
|

Pelaksanaan Program Badan Penyelenggara Jaminan Sosial Kesehatan Di Puskesmas Kabupaten Sidrap

Abstract: FKTP wajib menyelenggarakan pelayanan kesehatan komprehensif berupa pelayanan kesehatan promotif, preventif, kuratif, rehabilitatif, pelayanan kebidanan, dan pelayanan kegawatdaruratan, termasuk pelayanan penunjang yang meliputi pemeriksaan laboratorium sederhana dan pelayanan kefarmasian sesuai dengan ketentuan peraturan perundang-undangan yang berlaku. Penelitian ini bertujuan untuk mengetahui gambaran pelaksanaan (input, proses, output) program JKN di puskesmas Kabupaten Sidrap tahun 2020. Jenis penelitian … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…Studies on Indonesian children reported that factors that were related to the incidence of child stunting were children born with LBW, low parental height, low maternal education, male gender, living in urban areas and poor sanitation (Gunardi et al, 2017). It is imperative that health initiatives be implemented, including family planning (KB), health education for women and children (KIA), and the significance of maintaining a clean environment (Zulkarnain et al 2021).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies on Indonesian children reported that factors that were related to the incidence of child stunting were children born with LBW, low parental height, low maternal education, male gender, living in urban areas and poor sanitation (Gunardi et al, 2017). It is imperative that health initiatives be implemented, including family planning (KB), health education for women and children (KIA), and the significance of maintaining a clean environment (Zulkarnain et al 2021).…”
Section: Resultsmentioning
confidence: 99%
“…These were applied in the context of child protection, children's rights, including children with special needs (Kuntjorowati 2018). Health workers should also used media/tools for outreach/socialization to speed up the delivery of information to the outreach targets (Said et al, 2021).…”
Section: Discussionmentioning
confidence: 99%